Lean Six Sigma for Process Improvement in Software Development - Vorotnikova, Kateryna; Martínez, Felipe; Serhienko, Yaroslav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor's thesis aims to provide solutions for process improvement in software development, focusing on reducing bugs and improving delivery times through implementing Lean Six Sigma (LSS). Using process mapping, CTQ definition, FMEA, and Pareto analysis, the study identifies critical inefficiencies. The findings are used to suggest targeted improvements, like a Poka Yoke mechanism and a customized Kanban system. It is anticipated that these actions will decrease the Risk Priority Number (RPN) of top issues, reduce Lead Time, and increase First Time Yield. The control strategy ensures long-term sustainability of advancements by incorporating the 5W1H framework. This study presents the process of adapting LSS tools to software development and a reproducible model for optimizing other software development processes.
Vedoucí práce: Felipe Martínez
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses